Craniofacial Manifestations in Children with Hearing Loss: An Exploration of the Literature: Manifestasi Kraniofasial pada Anak dengan Gangguan Pendengaran: Tinjauan Literatur yang Komprehensif - Khaitova Dildora Sharipboevna (Universitas Muhammadiyah Sidoarjo, 2022)
This comprehensive study delves into the examination of magazines, scientific conference materials, and other reliable information sources to investigate the craniofacial region in children with hearing loss. Through meticulous research and analysis of various factors influencing craniofacial changes in this specific population, our objective was to identify significant findings and implications. Employing a systematic review approach, we synthesized data from diverse sources and evaluated the impact of these factors on craniofacial development. Our results shed light on the multifaceted nature of craniofacial alterations in children with hearing loss, highlighting the need for further research and providing valuable insights for clinicians and researchers involved in audiology, craniofacial sciences, and pediatric medicine. Highlights: The study focuses on investigating craniofacial manifestations in children with hearing loss through a comprehensive literature review. The research identifies reliable information sources and utilizes magazines, scientific conference materials, and related materials for data collection. The results provide valuable insights into the impact of various factors on the craniofacial region in children with hearing loss, highlighting the need for further research and implications for audiology and pediatric medicine. Keywords: craniofacial region, children, hearing loss, reliable information, literature review.